Strategically modified highly selective mitochondria-targeted two-photon fluorescent probe for Au3+ employing Schiff-base: Inhibited C=N isomerization vs. hydrolysis mechanism. (March 2018) - Wang, Wenjuan; Zhang, Wan; Feng, Yan; Wang, Shumin; Lei, Han; Huang, Jiali; Chu, Han; Li, Shanqing; Wang, Xin
Abstract: Strategic modifications from N -containing through O -containing to S -containing Schiff-base receptors lead to the development of a highly selective Au 3+ two-photon fluorescent probe that responded via an Au 3+ -induced hydrolysis mechanism. Here, we systematically demonstrate the two-step process of Au 3+ -induced hydrolysis reaction by implementing a series of well-designed experiments, which is of instructive significance for the structural design of Schiff-base receptors. The results reveal that Schiff-base receptors are first rapidly coordinated with Au 3+ (i.e. inhibited C=N isomerization mechanism), then hydrolyzed to the corresponding products by the attack of water. The rigid S -containing Schiff-base receptor (PyCM-3 ) has a better selectivity for Au 3+ than that of the flexible S -containing Schiff-base receptor (PyCM-2 ), which is supported by experimental and DFT results. Confocal fluorescence imaging experiments indicate thatPyCM-3 can be applied to monitor Au 3+ in mitochondria, fresh liver tissues and live zebrafishes under two-photon excitation with large two-photon action cross-sections, little cytotoxicity and good biocompatibility. Graphical abstract: Highlights: A pair of S -containing Schiff-base receptors for monitoring Au 3+ was developed. The two-step process of Au 3+ -induced hydrolysis mechanism was clearly proved. PyCM-3 showed a high selectivity to Au 3+ via the modification of Schiff base receptor. PyCM-3 could visualize Au 3+ in vitro and in vivo under two-photon excitation.